A study of growth failure and its related factors in children from 0 to 2 years in Tehran, Iran - Kholdi, Nahid; Zayeri, Farid; Bagheban, Alireza Akbarzadeh; Khodakarim, Soheila; Ramezankhani, Ali (The Turkish Journal of Pediatrics, 2012)
In this study, we aimed to estimate the prevalence of growth failure and identify the risk factors for this health problem in infants under two years old in Tehran, Iran. Using a cluster sampling method, 2182 infants' health files were randomly selected from eight health centers in Tehran. Growth failure was defined as a decrease in a child's weight (minimum 50 grams) at each attendance compared to the previous evaluation. The prevalence rate was between 0.05% and 6.2% at the different measurements. The regression analysis revealed that the presence of diarrhea [odds ratio (OR): 4.01, 95% confidence interval (CI): (3.50, 4.60)], respiratory infections [OR: 4.95, 95% CI: (4.40, 5.57)] and urinary tract infections [OR: 6.35, 95%CI: (3.97, 10.18)], as well as discontinuation of breast-feeding [OR: 10.91, 95%CI: (7.82, 15.23)], teething [OR: 4.14, 95% CI: (3.61, 4.75)] and complementary feeding [OR: 9.58, 95% CI: (6.48, 14.18)] were the significant risk factors for growth failure. Generally, our study showed a high prevalence of growth failure in infants less than two years in Tehran. More efforts are needed for promoting the knowledge level of mothers and healthcare providers to control this health problem in Iran.